A survey on the activities carried out by the English club in five secondary school in Kuching, Sarawak - Jeremy Jeff, Shahruddin (Universiti Malaysia Sarawak, UNIMAS, 2009)
The aim of this study is to survey the activities organized by the English Club in selected school in the Kuching division.English club is one of the co-curriculum activities in school. This study will look into the activities organised by the English Club and how the students’ response to the activities organised. There are 5 secondary school selected for the purposed of this study which focusing on the school in Kuching division. The method used for this study is survey by distributing questionnaire to the members of the English club. The findings of the study indicate that there are lots of activities organized by the club but most of the activities organized by the club in the schools that involve in this study are almost similar. This study also reveals how is the members of the club reacted to the activities organized by the club in the year 2008.